2015
DOI: 10.1093/fampra/cmv101
|View full text |Cite
|
Sign up to set email alerts
|

Electronic mail communication between physicians and patients: a review of challenges and opportunities

Abstract: Although promising benefits hold for email communication between physicians and patients in terms of lowering the costs of health care while maintaining or improving the quality of disease management and health promotion, physician use of email with patients is still low and lags behind the willingness of patients to communicate with their physicians through email. There is also a discrepancy between physicians' willingness and actual practice of email communication. Several factors may explain these discrepan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 36 publications
0
52
1
14
Order By: Relevance
“…16,46 In a study by Geryk et al (2016), the parents of children with asthma reported "recording data, physician communication, and sharing data via e-mail" and physicians reported "reminder for physician appointment" as the most important functionalities of the applications. 47 But because of the difference in targeting groups, asynchronous communication via e-mail and lack of sufficient time for physicians to connect to the internet, 48,49 this functionality was different in our study than in previous studies. Therefore, in this study, e-mail is not a good medium for interactions between patients and physicians in the viewpoints of experts.…”
Section: Discussioncontrasting
confidence: 60%
“…16,46 In a study by Geryk et al (2016), the parents of children with asthma reported "recording data, physician communication, and sharing data via e-mail" and physicians reported "reminder for physician appointment" as the most important functionalities of the applications. 47 But because of the difference in targeting groups, asynchronous communication via e-mail and lack of sufficient time for physicians to connect to the internet, 48,49 this functionality was different in our study than in previous studies. Therefore, in this study, e-mail is not a good medium for interactions between patients and physicians in the viewpoints of experts.…”
Section: Discussioncontrasting
confidence: 60%
“…Several studies identified technical barriers to the implementation of digital models of engagement, with one author citing 'the heavily firewalled, low bandwidth systems of the NHS' [Atherton H, Brant H, Ziebland S, Bikker A, Campbell J, Gibson A, et al The potential of alternatives to face-to-face consultation in general practice, and the impact on different patient groups: a mixed-methods case study. Health Serv Deliv Res 2018;6 (20). https://doi.org/10.3310/hsdr06200].…”
Section: Are There Differences In Synchronous and Asynchronous Models?mentioning
confidence: 99%
“…13,40 The increased utilisation of telephonic and e-mail communications may be attributable to widespread availability and use of technology by the general population, changing expectations for availability and timeliness of response, 45,46 and growing (but still low) physician comfort with electronic communications within their care processes. 47 However, these patient care options are not traditionally reimbursed by third party payers; we did not ask physicians if they were charging ancillary care fees for these services. Greater use of group visits was also observed.…”
Section: Discussionmentioning
confidence: 99%